Conservation biology of endemic species in Netherlands (Zoological Records and Reviews, 2024)
True endemism -- the restriction of a species to a single nation's territory -- is uncommon in the Netherlands given itsgeographic position, flat topography, and connectivity with the broader North Sea and Continental European fauna.Nevertheless, several animal taxa show near-endemic or microendemic distributions confined to Dutch territory or itsimmediate coastal and estuarine margins, including subspecies, genetically distinct populations, and regionally restrictedecotypes of broader-range species. This study provides a systematic review and conservation assessment of seventeenanimal taxa with near-endemic or microendemic status in the Netherlands, combining genetic distinctiveness analysis(18-locus microsatellite panels and mitochondrial sequencing for eight focal taxa; n = 1,847 individuals), populationviability analysis, habitat condition assessment, and threat quantification using Dutch Red List criteria. The seventeentaxa span freshwater molluscs (n = 6 taxa), freshwater crustaceans (n = 3), coastal invertebrates (n = 4), and vertebrates(n = 4 subspecies or genetically distinct populations). Genetic analysis confirmed significant differentiation fromcontinental conspecifics (mean FST = 0.28 +- 0.06 across eight focal taxa), supporting subspecific or evolutionarilysignificant unit (ESU) status for six taxa. Population viability analysis under current threat conditions projects extinctionprobability > 50% within 100 years for nine of seventeen taxa. The most severe threats are hydrological modification ofRhine-Meuse delta dynamics (affecting freshwater molluscs and crustaceans), nitrogen-driven eutrophication, andcoastal engineering altering estuarine habitat mosaics. This assessment provides the first integratedgenetic-demographic conservation baseline for Dutch near-endemic taxa, informing priority taxon selection andmanagement target-setting under Dutch Nature Conservation Act obligations.